2012
DOI: 10.4236/psych.2012.39104
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between People with Aphasia and Their Proxies on Health-Related Quality of Life after Stroke, Using the Greek SAQOL-39g

Abstract: Health related quality of life (HRQL) measures are increasingly used to evaluate stroke interventions. People with severe aphasia after stroke may be unable to self-report on such measures, necessitating the use of proxy respondents. This study explored the level of agreement between people with aphasia and their proxies on the Greek Stroke and Aphasia Quality of Life Scale-39 generic version (SAQOL-39g) and whether this agreement was influenced by proxy levels of depression and carer strain. Methods: Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…We did not find a significant difference between the SAQOL-39-TR total scale scores and those of subtests of proxies of individuals with aphasia. These results are in parallel to the results of some research [23,27,28]. However, it differs from results of a research [26], which suggests that psychological conditions of proxies of individuals with aphasia have impact on the agreement between the individual with aphasia and his/her proxy.…”
Section: The Correlation Between Saqol 39-tr Scale Scores Of Proxies Of Individuals With Aphasia and Caregiversupporting
confidence: 73%
See 2 more Smart Citations
“…We did not find a significant difference between the SAQOL-39-TR total scale scores and those of subtests of proxies of individuals with aphasia. These results are in parallel to the results of some research [23,27,28]. However, it differs from results of a research [26], which suggests that psychological conditions of proxies of individuals with aphasia have impact on the agreement between the individual with aphasia and his/her proxy.…”
Section: The Correlation Between Saqol 39-tr Scale Scores Of Proxies Of Individuals With Aphasia and Caregiversupporting
confidence: 73%
“…However, further research is needed on that variable. Ignatiou, et al examined the agreement of the health-related quality of life reports of proxies and those of individuals with aphasia by adapting the SAQOL-39 scale for Greece, it is known as SAQOL-39g [28]. Results of this study were in parallel to those of Hilari, et al [23].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a study performed using Greek SAQOL-39 generic version, reports by proxies rater who has regular contact with the patient is capable of providing information similar to that provided by the patient. 17 Therefore, family members or caregivers were encouraged to participate and support in the interview for the subjects with severe aphasia who are incapable of participating in the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, caution is needed when proxies contribute to QoL assessments. Nonetheless, when patient reports cannot be obtained, proxies can be helpful [ 67 ]. In the current study, the findings indicated that QoL did not significantly change in three participants because of the treatment.…”
Section: Discussionmentioning
confidence: 99%